SYNTHESIS AND ANTIMICROBIAL EVALUATION OF 2-[(SUBSTITUEDPHENYL)-5-(1-PHENYL-3-(PIPERAZINYL)PYRIDO[3,2-f]QUINAZOLIN-4(1H)-YL]-1,3,4-THIADIAZOLES - Ram, Tilak; Dubey, Ranjana; Chaudhary, Nidhi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
Several novel 2-[(substitutedphenyl)-5-(1-phenyl-3-(piperazinyl)pyrido[3,2-f] quinazolin-4(1H)-yl]-1,3,4 thiadiazole derivatives have been designed and synthesised by incorporating four known moieties such as 2-methylquinolin-5-ol, acetophenone, urea and 3-substitutedphenyl-4-amino-5-mercapto triazoles by using multi-step conventional reaction strategy. The synthesized derivatives were characterized by IR, 1H-NMR, Mass and elemental analysis (C, H, N). Furthermore the synthesized 2-[(substitutedphenyl)-5-(1-phenyl-3-(piperazinyl)pyrido[3,2-f]quinazolin-4(1H)-yl]-1,3,4-thiadiazoles 4a-g were screened for antibacterial and antifungal activities. The bacterial panel consisted of Staphylococcus aureus, Escherichia coli, Klabsiella pneumoniae, Proteus vulgaris while fungal panel included of Aspergillus fumigatus (plant isolate), Candida glabrata, Candida albacans, Candida krusei. Ampicillin trihydrate and fluconazole were used as reference drugs for antibacterial and antifungal activity respectively. Bacterial and fungal inhibition determined by disk diffusion and serial plate dilution method respectively. Pathogenic inhibitions were determined by measuring the diameter of the inhibition zone in mm. Compound 4c demonstrated significant antibacterial and antifungal spectrum against all the tested microbes.Keywords- antibacterial, antifungal and substituted 1,3,4-thiadiazoles.